Developing the Ideas of the Scientific School of L. S. Vygotsky: Scientific Publications of the Journal “Cultural and Historical Psychology” (2005-2016) (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
he article presents the analysis of the development of the ideas of L.S. Vygotsky’s school using the example of the publications in the international scientiﬁc journal “Cultural and Historical Psychology” (for the period 2005 through 2016). Over the period from 2005 to the end of 2016, 595 articles of 524 authors from 32 countries have been published in the journal “Cultural and Historical Psychology.” The study of the subjects of the articles published in the journal was held within the framework of the following criteria: scientometric publication indicators; group of authors; themes of the publications; relevance of the articles for their readers. The research uses the following sources: Russian Science Citation Index (RSCI); repository data of the psychological editions of https://psyjournals.ru/; report data on the activities of the journal “Cultural and Historical Psychology.” The citation frequency of the journal’s publications peaks in 2007, 2009 and 2006. Empirical ﬁndings comprise major part of the publications. The most developed areas are the studies of speech and thinking, personality, and communication.
Keywords: Cultural and historical psychology; L. S. Vygotsky; Bibliometric analysis; Web of science; RSCI; Speech; Personality; Socialization; Scientific publications